Preliminary findings on the volatile oil obtained from the fresh leaves of Citron Citrus medica L. (Fam. Rutaceae) - Makapugay, Helena C.; Castillo, Amorita V.; Concepcion, Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
The fresh leaves of Citrus medica L. was found to contain 0.3% essential oil and 74.5% moisture. The physical and chemical properties of the oil were determined.
The Abbe refractometer was used to determine the refractive index of the oil and the solubility of the oil in different solvents was also determined.
The sample was subjected to UV. The maximum wavelength of the oil as shown in the UV was compared with those of the standard reference and the different components determined.
Thin layer chromatography was employed in the isolation of constituents using pure benzene as the solvent systems. This was done in 5x15mm. glass plates.
A thin layer choromatography was also done on a 20x20 mm. plate wherein the sample oil was spotted alongside spots of standard references. This was followed by a preparative TLC but was not successful since bands were too close together for proper scraping.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1978.
Keywords: Citrus oils